2015
DOI: 10.1136/bmjopen-2015-008222
|View full text |Cite
|
Sign up to set email alerts
|

A journey into a Mediterranean diet and type 2 diabetes: a systematic review with meta-analyses

Abstract: ObjectivesTo summarise the evidence about the efficacy of a Mediterranean diet on the management of type 2 diabetes and prediabetic states.DesignA systematic review of all meta-analyses and randomised controlled trials (RCTs) that compared the Mediterranean diet with a control diet on the treatment of type 2 diabetes and prediabetic states was conducted. Electronic searches were carried out up to January 2015. Trials were included for meta-analyses if they had a control group treated with another diet, if they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
242
3
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 416 publications
(274 citation statements)
references
References 51 publications
14
242
3
15
Order By: Relevance
“…The protective effect of the Mediterranean diet against the development of diabetes has been consistently demonstrated and various mechanisms have been implicated, including improvement of insulin sensitivity, reduction of endothelial dysfunction and inflammatory markers, and increase in antioxidant markers [5,16]. The antidiabetic effect of the Mediterranean diet in the non-diabetic population of the ATTICA cohort was mediated by attenuation of inflammation and enhancement of total antioxidant capacity [6].…”
Section: Level Of Adherence To the Mediterranean Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…The protective effect of the Mediterranean diet against the development of diabetes has been consistently demonstrated and various mechanisms have been implicated, including improvement of insulin sensitivity, reduction of endothelial dysfunction and inflammatory markers, and increase in antioxidant markers [5,16]. The antidiabetic effect of the Mediterranean diet in the non-diabetic population of the ATTICA cohort was mediated by attenuation of inflammation and enhancement of total antioxidant capacity [6].…”
Section: Level Of Adherence To the Mediterranean Dietmentioning
confidence: 99%
“…-Moderate consumption of wine, fish, and dairy products. -Low consumption of poultry, meat, highly processed foods, refined grains, and sugars [5].…”
Section: Introductionmentioning
confidence: 99%
“…Many of these proposed mechanisms are, at least partially, modifiable with dietary interventions involving the MedDiet. For example, recent meta-analyses of RCTs have shown that when comparing with a variety of control diets, a Mediterranean style diet has beneficial effects on glycemic control, weight loss and cardiovascular risk factors among individuals with T2DM [160,161]. Furthermore, recent results from the long term MÉDITA trial showed that when compared with a standard low-fat diet, a Mediterranean diet ameliorates the inflammatory response and improves endothelial functioning in persons with T2DM [162,163].…”
Section: Implications For Future Research and Conclusionmentioning
confidence: 99%
“…Most studies of the Mediterranean diet in the context of type 2 diabetes and CVD have shown favorable effects on glycemic control and CVD risks, although there is some controversy about obesity [86,87] . A recent 4-year prospective cohort study examined the relationship between the Mediterranean diet and mortality in individuals with type 2 diabetes.…”
Section: Translating Dietary Recommendations To Food-based Guidelinesmentioning
confidence: 99%